Estruturação de dados para BIM FM em edificações públicas: estudo de caso na Universidade Federal de Uberlândia - Reis, João Vitor dos (2024)
The BIM-FM methodology combines digital building modeling with facility management, enhancing operation and maintenance throughout the project's lifecycle. Decisions are primarily data-driven, and by consolidating detailed and updated information about the building, it is possible to improve operational efficiency and reduce maintenance costs. Through a Systematic Literature Review, a knowledge gap was identified regarding which data in a BIM-FM Model are relevant to the activities of FM professional teams in a public building. Consequently, this study aimed to structure information for the management and maintenance of public buildings through an as-is BIM model as a database, to identify challenges and opportunities associated with this methodology. Adopting a case study strategy, unstructured interviews and questionnaires were conducted with professionals responsible for managing facilities and maintenance to identify the relevant data for these sectors' activities. The study object was the university blocks 1Y and 5E of the Santa Mônica campus of the Federal University of Uberlândia, for which models were developed in architectural, structural, plumbing, and electrical disciplines, along with the respective FM data obtained from data collection through interviews and questionnaires. It was concluded that BIM modeling for FM is challenging, requires significant time, and deals with large amounts of information. Additionally, the use of technologies such as photogrammetry facilitates the work. The study demonstrated that integrating maintenance data into the BIM model enhances the visualization and availability of information for the management of facilities in public buildings.